2021
DOI: 10.1093/molbev/msab158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Origins and Sex-Biased Admixture of the Huis

Abstract: The Hui people are unique among Chinese ethnic minorities in that they speak the same language as Han Chinese (HAN) but practice Islam. However, as the second-largest minority group in China numbering well over 10 million, the Huis are under-represented in both global and regional genomic studies. Here, we present the first whole-genome sequencing effort of 234 Hui individuals (NXH) aged over 60 who have been living in Ningxia, where the Huis are mostly concentrated. NXH are genetically more similar to East As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
10
33
0
Order By: Relevance
“…The close genetic affinity among Chinese Turkic speakers, Tungusic, and Mongolic populations indicated the probability of common ancestor of Altaic speakers. Our results showed that both West and East Eurasian contributed the genetic formation of Altaic populations in Northwest China, which coinciding with previous studies suggested the east-west admixture in Alatic populations and Hui population ( Xu and Jin, 2008 ; Bai et al, 2018 ; Jeong et al, 2019 ; Zhao et al, 2020 ; Ma et al, 2021 ). The closer genetic relationship between our studied population and Sino-Tibetan populations and the results of qpAdm and GLOBETROTTER suggested the majority contributing East Eurasian ancestry might derived from millet farmers in Yellow River Basin related population.…”
Section: Discussionsupporting
confidence: 91%
“…The close genetic affinity among Chinese Turkic speakers, Tungusic, and Mongolic populations indicated the probability of common ancestor of Altaic speakers. Our results showed that both West and East Eurasian contributed the genetic formation of Altaic populations in Northwest China, which coinciding with previous studies suggested the east-west admixture in Alatic populations and Hui population ( Xu and Jin, 2008 ; Bai et al, 2018 ; Jeong et al, 2019 ; Zhao et al, 2020 ; Ma et al, 2021 ). The closer genetic relationship between our studied population and Sino-Tibetan populations and the results of qpAdm and GLOBETROTTER suggested the majority contributing East Eurasian ancestry might derived from millet farmers in Yellow River Basin related population.…”
Section: Discussionsupporting
confidence: 91%
“…The most natural selection marker was SNP rs11966200 located in SLC44A4 in chromosome 6, which was associated with susceptibility of postlingual non-syndromic mid-frequency hearing loss ( Ma et al, 2017 ). SNP rs4148211 located in ABCG8 (iHS: –0.1227 and nSL: 0.0538 in Guizhou Hans) was also one identified SNP that possessed high genetic differentiation between Huis and Hans ( Ma et al, 2021 ), but which is not significant in our studied Hans. Among 83 SNPs, we identified 15 SNPs with the natural selection signals (iHS < –1) located in ABCG1 or ABCG2 associated with the regulation lipid metabolism, especially for SNP rs3788008 (iHS: –2.1567).…”
Section: Discussionmentioning
confidence: 54%
“…All of them except SNP rs72939934 harbored nSL values ranging from 1.1930 to 1.4646. SNP rs3827760, one variation being recently evidenced harboring greater genetic differentiation between Gansu Huis and Hans ( Ma et al, 2021 ), also had relatively high natural selection signals in Guizhou Hans (iHS: 1.1139 and nSL: 1.2567). Among 3,133 SNPs located in the Solute Carrier Family (SLC) genes, we identified 70 loci that had large iHS values larger than 1 and 527 SNPs less than –1.…”
Section: Discussionmentioning
confidence: 98%
“…To construct a paternal and maternal genealogy of HNL, we classified NRY haplogroups using Y-LineageTracker v1.3.0 ( Chen et al 2021 ) based on the ISOGG Y-DNA tree v2019-2020 ( https://isogg.org/tree ), and mtDNA haplogroups using HaploGrep v2.1.16 ( Weissensteiner et al 2016 ) based on a PhyloTree mtDNA tree v17 ( https://www.phylotree.org/tree ; Van Oven 2015 ). To investigate the population structure at paternal and maternal levels more comprehensively, we also collected NRY and mtDNA haplogroup data of East Asian and Southeast Asian populations from published research ( Kong et al 2003 ; Wen et al 2005 ; Hammer et al 2006 ; Hill et al 2007 ; Li, Cai, et al 2007 ; Li, Zhong, et al 2007 ; Jin et al 2009 ; Li et al 2010 ; Zhao et al 2010 ; Delfin et al 2012 , 2014 ; Ko et al 2014 ; Trejaut et al 2014 ; 1000 Genomes Project Consortium 2015 ; Lu et al 2016 ; Poznik et al 2016 ; Song et al 2019 ; Gao et al 2020 ; He et al 2020 ; Ma et al 2021 ) for comparison ( supplementary tables S4 and S5, Supplementary Material online) and performed PCA based on haplogroup frequency. We also calculated the haplogroup diversity for each population following the formula: , where n is the sample size of each population and x is the frequency of each haplogroup in each population.…”
Section: Methodsmentioning
confidence: 99%